Uncovering steroidopathy in women with autism: a latent class analysis - Pohl, Alexa (BioMed Central, 2014)
BACKGROUND: Prenatal exposure to increased androgens has been implicated in both polycystic ovary syndrome (PCOS) and autism spectrum conditions (ASC), suggesting that PCOS may be increased among women with ASC. One study suggested elevated steroidopathic symptoms (‘steroidopathy’) in women with ASC. As the symptoms are not independent, we conducted a latent class analysis (LCA). The objectives of the current study are: (1) to test if these findings replicate in a larger sample; and (2) to use LCA to uncover affected clusters of women with ASC. METHODS: We tested two groups of women, screened using the Autism Spectrum Quotient - Group 1: n = 415 women with ASC (mean age 36.39 ± 11.98 years); and Group 2: n = 415 controls (mean age 39.96 ± 11.92 years). All participants completed the Testosterone-related Medical Questionnaire online. A multiple-group LCA was used to identify differences in latent class structure between women with ASC and controls. RESULTS: There were significant differences in frequency of steroid-related conditions and symptoms between women with ASC and controls. A two-class semi-constrained model best fit the data. Based on response patterns, we identified the classes as ‘Typical’ and ‘Steroidopathic’. The prevalence of the ‘Steroidopathic’ class was significantly increased within the ASC group (ΔG(2) = 15, df =1, P = 0.0001). In particular, we confirmed higher frequencies of epilepsy, amenorrhea, dysmenorrhea, severe acne, gender dysphoria, and transsexualism, and differences in sexual preference in women with ASC. CONCLUSIONS: Women with ASC are at increased risk for symptoms and conditions linked to steroids. LCA revealed this steroidopathy despite the apparent underdiagnosis of PCOS.